Optimizing Guidance and Counseling Services to Address The Impact of Gadget Use on Elementary School Students' Social Skills - Rahman, Maulida Aulia; Sinta, Siti; Ajijah, Siti Nur (Institut Agama Islam Negeri Curup, 2024)
Children today spend more time playing with their gadgets than with other people in their immediate environment. This phenomenon can lead to problematic interpersonal and communicative skills that cause children to distance themselves from social life, which can lead to antisocial behavior. The problems caused are contrary to the dimensions of psychological well-being, that positive relationships with others and control over the environment. Guidance and counseling services can act as a solution to optimize social skills in children. The research conducted examines the ability of social interaction of children who use gadget, and the efforts of classroom teachers to provide guidance and counseling services to develop positive social skills in students at school. The research approach used is qualitative with the research design used is a case study at SDN 1 Sukagalih and SDN 1 Cikedokan. The research instruments were interview guide, observation guide, questionnaire and records of activities at school. The results showed that the ability of social interaction was in the enough category and the class teacher has an important role in guidance because the class teacher has more time than other teachers and has the obligation to shape the personality of students in accordance with values and morals to improve the students' character. Based on research findings and literature studies on the role of guidance and counseling services in optimizing social skills can be arranged by considering the principles of intervention, classroom conditioning, emotional relationships between teachers and children, and teacher characteristics. The service is implemented by the classroom teacher and integrated into the school program.